Wisdom and its Implication in the Priestly Formation Context - Erwin Sasmito (Journal of Asian Orientation in Theology, 2021)
Wisdom is defined in a variety of meanings in accordance with the times. Understanding wisdom originated from philosophical approaches. After these philosophical views, wisdom is understood in the psychology context. Wisdom has received increasing attention in empirical research in recent years, especially in gerontology and psychology. Wisdom generally is associated with older people. Modern empirical research has no significant reason to believe that wisdom is solely owned by older people. Wisdom is not a result of aging per se, but rather, only those older people who use their lifetime experiences optimally tend to acquire wisdom with aging. In this paper, wisdom is defined as human’s multidimensional abilities which can be learned and measured, and increases with age through advanced cognitive and emotional development which is driven by experience. Multidimensionality of wisdom (e.g. practical, reflective, openness interactional, paradoxical, ethical sensibility and experience) shows that wisdom is not always related with older age, but refers to the individual’s abilities to reason carefully; to reminisce and reflect; to tolerate with alternative views; and to regulate own emotional and expressions). The definitions lead to the implication that family and seminary formation have chance to develop the wisdom as human’s multidimensional abilities.